Integrative Conservation Management Of Bornean Orang Utan (Pongo Pygmaeus) In Malaysia - Abd Mutalib, Aini Hasanah (2020)
Conservation management of orang utan in Malaysia is a very crucial issue since Bornean orang utan is categorized to Critically Endangered (CR) status by IUCN since 2016. This thesis encompassed four elements of conservation which are behavior of the orang utan, nesting ecology of the orang utan, the human-wildlife interaction and technology feasibility. The objectives of the thesis were firstly, to determine the difference between behavioral pattern, and space use based on absence and presence of visitors, and also visual direction during presence of visitors, by using focal sampling at SORC, SNR and Taiping Zoo. Secondly, this thesis aimed to determine the nesting site preference (nesting site, classes, position, tree species used for nesting, tree height, and DBH) by orang utans in SORC and SNR The variation of nest structure quantitatively (length, depth, width and temperature factor) in SORC and SNR are studied by utilizing Unmanned Aerial Vehicle (UAV) integrated with open-resource software.